Tuberkulosis Paru Relaps - Gina Sonia Rahmah; Puspa Rosfadilla (Lembaga Pengembangan Kinerja Dosen, 2025)
Relapsing Pulmonary Tuberculosis is a patient with pulmonary TB who has received TB treatment and has been declared cured or finished treatment, then re-diagnosed as positive pulmonary TB through BTA examination or sputum culture by Mycobacterium tuberculosis. In high incidence settings, this figure is as high as 7850 cases/100000 person-years. A 66 year old patient came to the emergency room at Cut Meutia Hospital with complaints of coughing up blood which had been felt since 3 days SMRS, and worsened after 1 day SMRS, phlegm was fresh red, blood was mixed with phlegm when coughing. Previously the patient had been coughing up phlegm without blood since 2022 coughing felt to come and go. The patient also complained of chest pain on the right side, shortness of breath when doing activities, the patient also complained of night sweats that soaked clothes and bed, denied nausea, vomiting, defecation and urination. there were no complaints, the patient had a history of DM. On physical examination it was found that the patient's general condition appeared to be moderately ill, consciousness was compos smentis, blood pressure was 110/70 mmHg, pulse rate was 66x/minute, respiration was 22x/minute, with a body temperature of 36.7°C and SpO2 98% on room air. Auscultation revealed vesicular breathing sounds (+/+), rhonchi (-/-), wheezing (-/-). Blood laboratory examination: HB decreased (12.00), MCV decreased (76.78 fL), MCH decreased (23.2 pg), MCHC decreased (30.30 thousand/uL).